A comparison of anthropometric and training characteristics between female and male half-marathoners and the relationship to race time - Friedrich, M.; Rüst, C. A.; Rosemann, T.; Knechtle, P.; Barandun, U.; Lepers, R.; Knechtle, B. (Asian Journal of Sports Medicine, 2014)
Purpose: Lower limb skin-fold thicknesses have been differentially associated with sex in elite runners. Front thigh and medial calf skin-fold appear to be related to 1,500m and 10,000m time in men but 400m time in women. The aim of the present study was to compare anthropometric and training characteristics in recreational female and male half-marathoners.